2016
DOI: 10.5230/jgc.2016.16.3.131
|View full text |Cite|
|
Sign up to set email alerts
|

Korean Gastric Cancer Association Nationwide Survey on Gastric Cancer in 2014

Abstract: PurposeThe Korean Gastric Cancer Association (KGCA) has conducted nationwide surveys every 5 years, targeting patients who received surgical treatment for gastric cancer. We report the results of the 2014 nationwide survey and compare them to those of the 1995, 1999, 2004, and 2009 surveys.Materials and MethodsFrom March 2015 to January 2016, a standardized case report form was sent to every member of the KGCA via e-mail. The survey consisted of 29 questions, regarding patient demographics as well as tumor-, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(75 citation statements)
references
References 18 publications
1
74
0
Order By: Relevance
“…According to the results of this study, the detection rate of early GC (T1) has increased each year among the three phases, from 3.9% in Phase 1 to 14.4% in Phase 3 ( P = 0.000), which is partly attributed to accurate diagnostic methods, equipment support, and people’s strengthening of the concept of early diagnosis and early treatment. This is similar to the results of studies in Western countries[ 13 ] but still far from the respective 61% and 58% diagnostic rates reported by South Korea and Japan, which have already conducted early GC screening programs[ 40 , 41 ]. In this study, open surgery was one of the criteria, and the study did not include patients who underwent endoscopic resection (such as endoscopic mucosal resection and endoscopic submucosal dissection).…”
Section: Discussionsupporting
confidence: 88%
“…According to the results of this study, the detection rate of early GC (T1) has increased each year among the three phases, from 3.9% in Phase 1 to 14.4% in Phase 3 ( P = 0.000), which is partly attributed to accurate diagnostic methods, equipment support, and people’s strengthening of the concept of early diagnosis and early treatment. This is similar to the results of studies in Western countries[ 13 ] but still far from the respective 61% and 58% diagnostic rates reported by South Korea and Japan, which have already conducted early GC screening programs[ 40 , 41 ]. In this study, open surgery was one of the criteria, and the study did not include patients who underwent endoscopic resection (such as endoscopic mucosal resection and endoscopic submucosal dissection).…”
Section: Discussionsupporting
confidence: 88%
“…In Fareast Asia, including Korea and Japan, a higher proportion of EGC has been commonly detected in routine clinical. [ 48 , 49 ] Among those 27 included studies, we specially screened 8 EGC studies and found the pooled sensitivity was more frustrating: 0.34 (95% CI: 0.15–0.61). Fujikawa et al [ 27 ] reported the sensitivity was barely 0.04 (2/47) in clinical T1 staged GC in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic gastrectomy for gastric carcinoma yields better early postoperative outcomes including lesser pain, fewer wound complications, shorter hospital stays, and improved short-term quality of life than open surgery [ 1 2 ]. In Korea and Japan, early gastric carcinoma now accounts for nearly 50% of all gastric cancer cases, and laparoscopic gastrectomy is widely performed as a minimally invasive treatment [ 3 4 ]. The surgical techniques of laparoscopic distal gastrectomy, including gastric resection and lymph node dissection, are relatively well-standardized among gastric surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…With the rise in the aging population, the proportion of elderly patients who undergo gastric resection is continuously increasing. According to a Korean nationwide survey, the proportion of patients aged ≥70 years undergoing gastric cancer surgery has markedly increased from 9.1% to 25.3% in 1995 and 2014, respectively [ 3 ]. With increasing age, patients demonstrate a greater number of comorbidities such as hypertension, diabetes mellitus, and cardiovascular and pulmonary diseases.…”
Section: Introductionmentioning
confidence: 99%